Recognition and management of rapid-onset gluten ataxias: case series - Newrick, Laurence (Cerebellum Ataxias, 2021)
BACKGROUND: Most immune-mediated cerebellar ataxias, including those associated with gluten sensitivity (Gluten Ataxia), tend to present subacutely and usually progress gradually. Acute presentations with rapid progression outside the context of paraneoplastic cerebellar degeneration require prompt diagnosis and early access to disease-modifying immunotherapy in order to avert severe and permanent neurological disability. CASE PRESENTATIONS: We describe three cases of rapid-onset Gluten Ataxia, an immune-mediated cerebellar ataxia due to gluten sensitivity. We detail their presentation, clinical and neuroimaging findings, and our treatment strategy with immunotherapy. CONCLUSIONS: Our cases highlight the potential for immune-mediated cerebellar ataxias to present acutely, with rapid-onset symptoms and devastating neurological consequences. We caution against the diagnosis of ‘post-infective cerebellitis’ in adults, and advocate early consideration of an immune-mediated cerebellar ataxia and initiation of immunotherapy to prevent irreversible cerebellar damage.